THE EFFECT OF DIGITAL MARKETING ON PURCHASE INTEREST WITH CUSTOMER SATISFACTION AS A MODERATING VARIABLE - Yandri Ardolof Bowo Laksono Toar (LPSDI Bina Patria, 2024)
This study examines the influence of digital marketing on customer satisfaction and purchase intention, as well as the role of customer satisfaction as a moderating variable. The analysis indicates that the relationship between digital marketing and customer satisfaction is significant and positive, as is the relationship between digital marketing and purchase intention. Additionally, there is a significant and positive relationship between customer satisfaction and purchase intention. However, customer satisfaction is not effective in moderating the influence of digital marketing on purchase intention. These findings highlight the importance of digital marketing in enhancing customer satisfaction and purchase intention, even though customer satisfaction does not significantly alter the impact of digital marketing on consumer buying interest. This study provides insights for digital marketing practices in strategies to enhance customer satisfaction and its impact on purchasing behavior.